A design consideration for durability of high-performance concrete - Chang, P.K; Peng, Y.N; Hwang, C.L (Cement & concrete composites, 2001)
Environmental factors, especially the climate, have significant influence on concrete structure. This paper aims to investigate the harmful effects of maritime climate on the durability of concrete structures built in coastal areas. Singly reinforced beam specimens of traditional design and those of densified mixture design algorithm (DMDA) were employed to study the potential problems of concrete structure. Results indicate that cracks on the concrete structure, if go unnoticed, may cause failures. Thus, it is important to know the methodology of achieving high strength and durable concrete in order to avoid formation of cracks in the structural member.